Implementation of the Accelerated Stunting Handling Program - Pratidina, Ginung; Wahyudin, Cecep; Rahmawati, Rita; Ulfah Zakiah, Ratu; Handayani, Yeni; Noviani Alya Putri, Regita (Iapa Proceedings Conference, 2023)
The East Bogor District Government implemented an accelerated stunting handling program to reduce stunting. This research aims to evaluate the effectiveness of implementing the acceleration program for handling stunting in the East Bogor Regency. The research method used is descriptive quantitative research. Data was collected through interviews and questionnaires given to respondents. The collected data was analyzed using the Weight Mean Score (WMS) method to calculate the average score of respondents. The research results show that the program accelerates treatment stunting in East Bogor District, Bogor City, which is very good. The dimensions of communication, resources, attitude of implementers, bureaucratic structure, and provision of PMT and MPASI show an average score of 87%, included in the perfect criteria. In the PMT and MPASI dimensions, the average score reached 90%, indicating the program's success in terms of PMT and MPASI. These results show that the East Bogor District Government firmly understands the importance of appointing bureaucrats/program implementers, providing work motivation incentives, and responding well to statutory regulations. This research can be a basis for developing and improving treatment programs that are more effective in the East Bogor District and contribute to efforts to overcome problems in the region.